Description of personality characteristics and sociocultural dimensions in mexican youths - Palacios, Jorge Raúl (2017)
The aim of this study was to describe sociocultural dimensions and personality characteristics in Mexican youths. The sample was conformed by 121 university students between 18 and 37 years old (M= 21.34; SD= 2.6) of the state of Querétaro, México. In order to measure sociocultural and personality characteristics two open questions were used to obtain associated clusters. The results indicated that the sociocultural dimensions describe terms associated with traditionalism, values, norms, descriptions, economic tendency, perceptions and local processes. The personality characteristics show traits of agreeableness, social expressive, obedient-affiliative, affective expression (negative and positive), negative instrumentality, intellect, egocentric, rebelliousness, personal control and persistency. The discussion analyzes the utility of the results for the assessment of sociocultural and personality traits in youths, as well as the implications for future research in ethnopsychology.